2021
DOI: 10.11622/smedj.2020035
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of inhalational methoxyflurane (Penthrox®) and intramuscular tramadol for prehospital analgesia

Abstract: Online first papers have undergone full scientific review and copyediting, but have not been typeset or proofread. To cite this article, use the DOIs number provided. Mandatory typesetting and proofreading will commence with regular print and online publication of the online first papers of the SMJ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
(20 reference statements)
1
9
0
Order By: Relevance
“…In the prehospital setting comparing methoxyflurane with intramuscular tramadol in a cluster randomised cross-over trial for people with moderate to severe pain due to musculoskeletal trauma in Singapore, methoxyflurane was superior to tramadol in efficacy, speed of onset and administration, but with more minor adverse effects [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the prehospital setting comparing methoxyflurane with intramuscular tramadol in a cluster randomised cross-over trial for people with moderate to severe pain due to musculoskeletal trauma in Singapore, methoxyflurane was superior to tramadol in efficacy, speed of onset and administration, but with more minor adverse effects [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the extensive use of methoxyflurane in Australia and New Zealand for 40 years, only a few studies [18][19][20][21] have tested methoxyflurane with active comparators for acute pain management in patients with trauma. In the prehospital settings, a large retrospective study showed the analgesic effect of methoxyflurane was inferior to IV morphine and intranasal fentanyl, 18 whereas one randomized controlled trial versus intramuscular tramadol showed that methoxyflurane resulted in a significantly greater and faster reduction in pain score.…”
Section: Discussionmentioning
confidence: 99%
“…Although Low-dose Penthrox Inhaler (3 ml) can be simply given, it also quickly reduces pain compared to the administration of analsegic drugs by injection (Mercadante et al, 2019).Penthrox Inhaler inhalation gives a faster effect on pain reduction compared to Tramadol injection, Tramadol is an analgesic drug that is given by injection into the intramuscular (Lim et al, 2020).…”
Section: Picture 2:-workflow Penthrox Inhalermentioning
confidence: 99%